Pengaruh Pembelajaran Mendalam (Deep Learning) Dan Lingkungan Sekolah Terhadap Karakter Siswa Pada Mata Pelajaran Pendidikan Agama Kristen Di Kelas VIII SMp Negeri 3 Tarutung Tahun Ajaran 2025/206 - Liberto Ripan Petrus Hutagalung; Baginda Sitompul; Lasmaria Lumban Tobing (Journal of Innovative and Creativity, 2026)
The purpose of this study was to analyze 1) the effect of in-depth learning on students' character in the subject of PAK; 2) the effect of the school environment on students' character in the subject of PAK; and 3) the effect of in-depth learning and the school environment together on students' character. The method used in this study is an inferential quantitative method. The population was all 219 students of class VIII of SMP Negeri 3 Tarutung in the 2025/2026 Academic Year and a sample of 55 people was determined, namely 25% of the total population using a random sampling technique. The instrument trial was conducted on 35 students who were not included in the sample so that it was known that of the 75 questionnaire items tested, 70 research instruments were declared valid and reliable because they had met the validity and reliability value criteria. The results of the data analysis show that: 1) the Fcount value > Ftable is 48.705 > 3.15, thus it is known that there is a positive influence of deep learning on students' character in the subject of Christian Religious Education in class VIII of SMP Negeri 3 Tarutung. The influence is 47.9%, 2) the Fcount value > Ftable is 66.104 > 3.15, thus it is known that there is a positive influence of the school environment on students' character in the subject of Christian Religious Education in class VIII of SMP Negeri 3 Tarutung. The influence is 55.5%, and 3) the Fcount value > Ftable is 46.429 > 3.15, thus it is known that there is a positive influence together from deep learning and the school environment on students' character in the subject of Christian Religious Education in class VIII of SMP Negeri 3 Tarutung. The influence is 64.1%, thus Ha is accepted and H0 is rejected